The effects of peripherally-subacute treatment with irisin on hippocampal dendritogenesis and astrocyte-secreted factors - Kim, Mun-Hee; Leem, Yea-Hyun (Journal of exercise nutrition & biochemistry, 2019)
Fibronectin type III domain containing 5 (FNDC5)/irisin is an exercise-induced myokine, which contributes to cognitive functions. However, the relationship between the neuroprotective effects of FNDC5/irisin and hippocampal dendritic remodeling and astrocyte-secreted factors remains unclear. Therefore, we explored whether subchronic recombinant irisin treatment affected hippocampal morphology and some astrocyte-derived molecules. Mice were intraperitoneally injected with irisin (0.5 μg/kg/day) for seven days, followed by their sacrifice two days later. Hippocampal morphometric parameters were analyzed and pgc-1a, fndc5, bdnf, and some astrocyte-derived factors mRNA levels were measured. Dendritic length, arborization, and spine density were enhanced by irisin regimen in hippocampal CA1 and CA3 areas. Hippocampal pgc-1a, fndc5, and bdnf mRNA levels were significantly increased by irisin treatment. Moreover, hevin mRNA levels were significantly enhanced, whereas tgf-b1 levels downregulated by irisin treatment. FNDC5/irisin has dendritogenic activity probably through hevin induction and TGF-β1 suppression.